OPTIMIZATION OF LEARNING SUPERVISION WITH AN ISLAMIC SPIRITUAL INSIGHT - Sonedi, Sonedi; Bahrianoor, Bahrianoor (Prodi Teknologi Pendidikan Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2023)
The results showed that: (1) the supervision program for spiritually oriented learning at SMA Muhammadiyah 1 Palangka Raya went well and smoothly; (2) supervision technique. Spiritual insight learning in SMA Muhammadiyah 1 Palangka Raya uses supervision techniques for each student's behavior. Based on the discussion of the research results and the results of interviews from homeroom teachers, principals, and students, it shows that the spiritual value of Islam is indeed very well instilled by students, even from an early age, because it has many positive impacts on students, not only in the classroom. during the learning process, but also in the community or outside of school, even in the home/family environment. The subjects in this study were students of class XI SMA Muhammadiyah 1 Palangka Raya. In accordance with the phenomenon to be studied by researchers, relevant tools and data collection are needed. In this study, the data collection techniques used were observation and interviews. The desired achievement obtained in this study is the application used by the researcher to help answer the questions in this study.